Red Skin, White Masks: Culture and Identity in Leslie Marmon Silko’s Ceremony - Salima, BENABIDA (My University, 2017)
This study addresses the relationship between literature and the Amerindian cultural identity in Leslie Marmon Silko‘s Ceremony (1977). The selected novel questions the Native Americans sense of belonging during the mid of the twentieth century. It gives a truthful description of the homecoming war veteran from the Second World War. Tayo, a native soldier, who was deeply affected by his experience in this war, developed a sense of loss due to his fragmented identity as a half-breed. In this multidisciplinary endeavor, we are interested in exhibiting the evils of the white world and the syndromes of hybridity that plagued and troubled the Natives‘ life. The dissertation examines Silko‘s Ceremony from both stylistic and the thematic angles. The first chapter deals with the socio-historical context of the novel. It inspects the status-quo of the Native Americans and the events that surrounded the process of writing this literary text. Besides, the second chapter, attempts at illustrating Silko‘s usage of the Indian Oral traditions as a main structuring element. It tries also to explain Silko‘s politics of language in using the power of the written word; i.e. this part aims at inspecting and clarifying Silko‘s stylistic strategies. The third chapter examines the psychology of the oppressed Native Americans, namely the war veterans who were forced to wear the White mask. As well as, it illustrates the power of the acknowledgment of the past in healing the future through exhibiting the impetus of the Amerindian culture and its paramountcy in the modern world.
Keywords: Culture, Identity, Cultural Criticism, Psychoanalysis, Amerindians, Oral Traditions.